Optimal timing of relocation - Pereira, José Azevedo (2007)
In this paper we tackle the problem of the optimal relocation policy for a firm that faces two types of uncertainty: one about the moments in which new (and more efficient) sites will become available; and the other regarding the degree of efficiency improvement inherent to each one of these new, yet to be known, potential location places. In particular, we derive results concerning the expected optimal timing for relocation, the corresponding volatility and the value of the firm under the optimal relocation policy. Impacts on the final results driven by the characteristics of the firm´s original location site, the market environment and the way in which risk is modeled, are studied numerically. The overall results are in line with economic intuition